Novel SUN5 Mutation Associated with Acephalic Spermatozoa Syndrome: A Cross-sectional Study - Sarvenaz Alinia; Fatemeh Eskandari Chenari; Seyedeh-Hanieh Hosseini; Alemeh Rafaee; Amaneh Javid; Mohammad Ali Sadighi Gilani; Marjan Sabbaghian (Journal of Human Reproductive Sciences, 2025)
Background: The SUN5 gene encodes a testis-specific protein required for sperm head–tail connection during spermiogenesis. The SUN5 gene has an established role in the acephalic spermatozoa syndrome (ASS) defect recognised by headless tails, spermatozoa with disrupted head–tail junction and also a few tailless heads in semen. Aim: This study aims to evaluate the genetic variants of all exons of the SUN5 gene and the protein expression in 10 men with ASS. Settings and Design: This cross-sectional study was conducted on 10 infertile men with ASS as a case group and 10 men with normal spermogram as a control group referred to the Royan institute between 2015 and 2020. Materials and Methods: Polymerase chain reaction and Sanger sequencing were performed on DNA extracted from patients’ peripheral blood. In addition, immunocytochemistry and western blotting were accomplished to evaluate the SUN5 protein expression in the patient carrying a distinct exonic variation. Statistical Analysis Used: No statistical analysis was needed to be done in this survey. Results: Sequencing outcomes represented one homozygous missense mutation (c.1073G>A [p.Arg358Gln]) in exon 13 of the SUN5 gene in one patient with 98% acephalic spermatozoa in the total sperm population. This mutation did not exist in the control group. SUN5 protein expression was completely undetectable in the patient with c.1073G>A. Conclusion: Based on current results, it could be concluded that c.1073G>A detected mutations in the SUN5 gene could alter the SUN5 protein expression and lead to male infertility due to ASS.